Induction of Collagen I by CXCL10 in Ovarian Theca–Stroma Cells via the JNK Pathway - Wang, Chaojun; Sun, Yun (Frontiers in Endocrinology, 2022)
Premature ovarian insufficiency (POI) poses a great threat to reproductive-age women. Ovarian fibrogenesis is a basic histologic feature of POI. Ovarian theca-stroma cells are responsible for ovarian fibrosis but little studies attended to ovarian microenvironment. The role and mechanism of chemokines in the development of POI remain unclear. Here, we evaluated CXCL10 in bPOI patients, POI patents and in a POI mouse model. CXCL10 levels in serum and follicular fluid were higher in both bPOI and POI patients than in control people. Increased level of CXCL10 was also observed in a POI mouse model. CXCL10 concentrations in serum and follicular fluid were positively associated with follicle-stimulating hormone, and negatively associated with antral follicle count. Our study for the first time found that CXCL10 induced COL1A1 and COL1A2 production, two subunits of collagen I in mouse theca-stroma cells by activating JNK/c-Jun pathway. Inhibition of JNK and c-Jun attenuated the increase of COL1A1 and COL1A2 caused by CXCL10. Moreover, CXCL10 had no effects on hormone synthesis，proliferation and apoptosis in human luteinized granulosa (hGL) cells. Our findings revealed a diagnostic value of CXCL10 in early stage of POI and shed a new insight into the biological function of CXCL10 in ovarian fibrosis.